A temática resíduos sólidos e o programa escola SESI para o mundo do trabalho: uma proposta de situação de estudo interdisciplinar - Rodrigues, Amanda Fernandes dos Santos (2018)
The lack of meaning of knowledge, interaction with students and other colleagues, along with the exaggerated reproduction of content, limit the teaching-learning process and the exploration of relevant themes in the school context. In order to favor the student's fuller development, with active participation, with a critical vision, and wrapped in an interactive and contextualized process, the development of a Study Situation, in an interdisciplinary way, using a Solid Waste theme and the guidelines of the SESI School Program for the World of Work. To that end, the theoretical-methodological contribution involves the meaningful learning, from the sociocultural perspective, the role of social interactions in the classroom, the Three Pedagogical Moments, the interdisciplinarity, the thematic approach, and the teaching modality Study Situation. The research is qualitative, especially the typology of Case Study. The subjects of the research are students of a in High School, in a technical school, in the city of Catalão-GO. Records and productions in the course of the development of the Study Situation are the basis for the composition of the data. For the analysis of the process categories were elaborated: social interactions, interdisciplinary actions, problematization, awareness and conceptual signification. It can be affirmed that there was an improvement in the teaching-learning process when this occurred through social interactions (student-student and student-teacher) and the systematic confrontation of the paradigm of fragmented and linear teaching based on interdisciplinary and dynamic actions for the orientation of the curriculum of the different areas of knowledge, instigating the student in the approach of the school knowledge, providing cognitive development.